Business continuity management : towards an operational framework - Ng, Brandon Chee Khoon (2008)
The overall objective is for a continuing process to feed into a written "action plan", to be implemented when the (almost) unimagineable happens. BCM is taking reasonable steps in anticipation of unreasonable risks.